Significance Of Mobile Banking Services In Indonesia: Through The Impact Of Bca Syariah Customer Satisfaction And Loyalty - Pipit Larasati; Riyan Andni; M Fatchurrohman; Mohd Rushdan Yasoa; Nur Wulan Intan Palupi (Institute of Research and Community Service at Islamic University of Bunga Bangsa Cirebon, 2024)
This study was conducted at IAIN Kudus. The purpose of this study is to ascertain how Indonesian BCA Syariah customers' loyalty and level of satisfaction affects their use of mobile banking services. In order to conduct this study, quantitative methods were used. Customers of BCA Syariah in Indonesia make up the population used in this study; 106 samples were collected as responders. employing purposive sampling, a non-probability sampling technique. Respondents to the questionnaires were given out in order to collect data for this study. Following the collection of the data, data analysis was done using SPSS tools to process the results of validity and reliability tests, classical assumption tests, and hypothesis testing. Based on the findings of the analysis that was done, this study demonstrates that. Based on the t test, satisfaction and loyalty variables partially influence m-bankin services. And based on the F test, the variables of satisfaction and loyalty jointly influence mobile banking services.